Why users share marketer-generated contents on social broadcasting Web sites: A cognitive–affective involvement perspective. Issue 4 (2nd October 2017) - Li, Yuhao; Oh, Lih-Bin; Wang, Kanliang
ABSTRACT: As an emerging media platform, social broadcasting technologies provide users with a decentralized environment for producing and consuming information. This study develops a motivational model based on the cognitive and affective involvements of individuals to explore their intentions to share marketer-generated content (MGC). The model was empirically tested on 481 Sina Weibo users in a scenario-based environment. Results show that ad intrusiveness, anticipated rewards, category brand relevance, and brand attitude play important roles in facilitating cognitive and affective involvements. In turn, both types of involvement positively influence the intention of users to share MGC, but affective involvement yields a greater influence. Product types significantly moderate the relationship between the cognitive involvement of users and their intention to share MGC. Implications for research and practice are discussed.